Al-ʿAyn Oases Mapping Project: Jīmī Oasis (poster) - Power, Timothy; Sheehan, Peter (Proceedings of the Seminar for Arabian Studies, 2017)
Al-ʿ Ayn Oases Mapping Project is a collaboration between the Abu Dhabi Tourism and Culture Authority (TCA) and Zayed University. It aims to document the present oasis landscape and identify surviving historic components, while at the same time engaging Emirati students with their heritage and building capacity for archaeology in the UAE. The project utilizes a non-intrusive field-walking methodology suitable for a class of undergraduate students. The second season's work focused on Jīmī Oasis. Although the present configuration of the oasis dates to the late Islamic, earlier features in the landscape were found, probably dating to the early Islamic period and the Iron Age. The oasis seems to have been extended further to the west, which is understood to be part of a late nineteenth- and early twentieth-century revitalization of the oases under the leadership of the Āl Bū Falâḥ.